Visionary Leadership of the Principal of Senior High School (SMAN) 1 Pabuaran and Senior High School (SMAN) 1 Kalijati Subang West Java - Badrudin; Jakariya, Guntur (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
The visionary principal takes part in determining the quality of educational institutions. The problem is that not all principals are able to apply optimal visionary leadership. This study examines the strategy and characteristics of the visionary principal of SMAN 1 Pabuaran and SMAN 1 Kalijati. This is a qualitative study with the method of collecting the data is through observation, interview, and documentation study. The results of the study conclude that (1) the visionary strategy of the principal of SMAN 1 Pabuaran and SMAN 1 Kalijati is by formulating, transforming, and implementing the vision and missions so that they become a commitment of all stakeholders and emerging the sense of belonging and sense of ownership attitudes. (2) The characteristics of the visionary leadership of the principal of SMAN 1 Pabuaran and SMAN 1 Kalijati can be seen in their foresight, their ability to transform the vision into action, encourage their subordinates to work hard, motivate, and build a good relationship with the employees so that the concept of the vision is clearly accepted by the subordinate. The principal of SMAN 1 Pabuaran has a strong vision that affects the commitment of the subordinates to implement the vision, while the principal of SMAN 1 Kalijati could stimulate the self-leadership of the teachers so they are able to design work performance by using their own authority in making decisions.